2014
DOI: 10.1093/toxsci/kfu195
|View full text |Cite
|
Sign up to set email alerts
|

Glycodeoxycholic Acid Levels as Prognostic Biomarker in Acetaminophen-Induced Acute Liver Failure Patients

Abstract: Acetaminophen (APAP)-induced acute liver failure (ALF) remains a major clinical problem. Although a majority of patients recovers after severe liver injury, a subpopulation of patients proceeds to ALF. Bile acids are generated in the liver and accumulate in blood during liver injury, and as such, have been proposed as biomarkers for liver injury and dysfunction. The goal of this study was to determine whether individual bile acid levels could determine outcome in patients with APAP-induced ALF (AALF). Serum bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 40 publications
2
75
1
Order By: Relevance
“…GDCA in bile, as well as HDCA in serum were significant decrease and were selected as potential biomarkers for HSW induced liver injury. GDCA has been selected as biomarker in acetaminophen-induced acute liver failure in clinical study (Woolbright et al, 2014), Dietary HDCA exerted hypolipidemic effects by reducing farnesoid X receptor antagonist bile acids in mouse enterohepatic tissues (Watanabe and Fujita, 2014). Bile acids was synthesized in liver, and transported from hepatocytes into the biliary tracts by canalicular transporters, this process was sensitive to perturbation (Jaeschke et al, 2002; Yamazaki et al, 2013), which further confirmed that bile acids were highly sensitive markers for liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…GDCA in bile, as well as HDCA in serum were significant decrease and were selected as potential biomarkers for HSW induced liver injury. GDCA has been selected as biomarker in acetaminophen-induced acute liver failure in clinical study (Woolbright et al, 2014), Dietary HDCA exerted hypolipidemic effects by reducing farnesoid X receptor antagonist bile acids in mouse enterohepatic tissues (Watanabe and Fujita, 2014). Bile acids was synthesized in liver, and transported from hepatocytes into the biliary tracts by canalicular transporters, this process was sensitive to perturbation (Jaeschke et al, 2002; Yamazaki et al, 2013), which further confirmed that bile acids were highly sensitive markers for liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Bile acid measurements were performed as previously described in detail (Woolbright et al, 2014a). In brief, bile samples were first diluted 1:50 in water, whereas serum samples were used as is.…”
Section: Methodsmentioning
confidence: 99%
“…In 2012, a small retrospective study found that the Sequential Organ Failure Assessment (SOFA), evaluating multisystem dysfunction, is a better predictor than the King's College Criteria for identifying patients that will ultimately require transplantation, but again, further investigation is needed (Cholongitas et al 2012). Additional areas of promise for determining prognosis in acetaminophen-related ALF include individual bile acids such as glycodeoxycholic acid, markers of apoptosis such as M30, and indocyanine green (ICG) clearance (Milesi-Halle et al 2011;Rutherford et al 2012;Woolbright et al 2014). ICG clearance is a measure of the functional capacity of the liver and has shown positive correlation with extent of hepatic necrosis in murine models of acetaminophen hepatotoxicity (MilesiHalle et al 2011).…”
Section: Liver Transplantationmentioning
confidence: 99%